Associations Between Fathers' Work-to-Family Spillover and Their Ways to Track Children's Whereabouts and Doings: A Hong Kong Study. Issue 2 (June 2019) - Wong, Wai-lap Lance
Utilizing a Hong Kong Chinese sample, this study examined how fathers' negative work-to-family spillover was associated with their behaviors in monitoring their children's daily doings. In total, 125 fathers with a focal child at fifth or sixth grade were invited to complete a survey. Results revealed that work spillover was negatively associated with child self-disclosure, father solicitation, and father listening and observing children, and the associations for child self-disclosure and father solicitation were mediated by father–child relations. A marginally significant positive association between work spillover and getting information from spouse was also found. The results suggest that work stress poses difficulty to fathers in directly monitoring their children and pushes them to rely on mothers as the source of knowledge.